2015
DOI: 10.1161/jaha.115.001949
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin‐Dependent Kinase II Inhibition in Smooth Muscle Reduces Angiotensin II–Induced Hypertension by Controlling Aortic Remodeling and Baroreceptor Function

Abstract: BackgroundMultifunctional calcium/calmodulin-dependent kinase II (CaMKII) is activated by angiotensin II (Ang II) in cultured vascular smooth muscle cells (VSMCs), but its function in experimental hypertension has not been explored. The aim of this study was to determine the impact of CaMKII inhibition selectively in VSMCs on Ang II hypertension.Methods and ResultsTransgenic expression of a CaMKII peptide inhibitor in VSMCs (TG SM-CaMKIIN model) reduced the blood pressure response to chronic Ang II infusion. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 80 publications
2
35
1
Order By: Relevance
“…Here, we report that remodeling and constriction are concordantly increased with CaMKII inhibition. These data are not in agreement with the concept proposed by Folkow given that we previously reported that blood pressure is lower in TG SM-CaMKIIN mice following chronic Ang-II infusion as compared to WT mice [23]. However, other studies have emerged that that do not align with this concept [25].…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Here, we report that remodeling and constriction are concordantly increased with CaMKII inhibition. These data are not in agreement with the concept proposed by Folkow given that we previously reported that blood pressure is lower in TG SM-CaMKIIN mice following chronic Ang-II infusion as compared to WT mice [23]. However, other studies have emerged that that do not align with this concept [25].…”
Section: Discussioncontrasting
confidence: 69%
“…Chronic subcutaneous infusion of Ang-II (1.25 μg/kg/min, Anaspec) was performed using Alzet osmotic mini-pumps (model 1002, DURECT Corporation) as we previously reported [23]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an elegant genetic mouse model with vascular smooth muscle targeted CaMKII inhibition, the Grumbach group found that CaMKII activity contributes to the angiotensin II mediated hypertensive response in vivo, where it influences a complex and interconnected series of central and peripheral activities [52]. CaMKII is known to promote vascular smooth muscle hypertrophy [53] but this remodeling process is also affected by vascular smooth muscle death and migration.…”
Section: Vascular Diseasementioning
confidence: 99%